Antimicrobial Activity of Methanolic Extract of Merrimea gagentica and Litsea glutinosa Leaves - Meera, R.; Devi, P. (Asian Journal of Chemistry, 2010)
Methanolic extract of leaves of Merremia gagentica (MEMG) and Litsea glutinosa (MELG) were investigated for their in vitro antimicrobial properties by agar disc diffusion method. The crude methanolic extracts of MEMG and MELG inhibited the growth of both Gram positive bacteria (Bacillus subtilis, Staphylococcus aureus and Micrococcus luteus) and Gram negative bacteria (Escherichia coli, Pseudomonas aeruginosa and Salmonella typhimurium). The Gram positive bacteria tested appeared to be more susceptible to the extracts than the Gram negative bacteria. Both the extracts at the concentration range between 250 and 1000 μg/ mL showed inhibitory activity against all tested bacteria except MEMG which did not show activity against S. typhimurium at 250 μg/mL concentration. At 100 μg/mL concentration of MEMG was found neutral against Micrococcus luteus, Escherichia coli, Pseudomonas aeruginosa and Salmonella typhimurium while MELG was neutral against Escherichia coli and Pseudomonas aeruginosa at same concentration. The extracts also showed significant antifungal activity against Aspergillus niger and Candida albicans. All tested microorganisms showed dose dependent susceptibility towards the methanolic extracts. The antibacterial and antifungal activity of the extracts and standard drugs were statistically significant. Based on the current findings, it can be concluded that both the plants possess potent antimicrobial activity.